Tepid Modified Del Nido Cardioplegia in Adults Undergoing Cardiac Surgery: A Propensity-Matched Analysis - Sevuk,Utkan (2022)
Abstract Introduction: Del Nido cardioplegia was reported to provide adequate myocardial protection and clinical outcomes with improved surgical flow in adult cardiac surgical procedures. And many clinicians have already modified the traditional formula. This study aims to investigate the efficacy and safety of tepid modified del Nido cardioplegia compared to cold blood cardioplegia in adult patients undergoing cardiac surgery. Methods: This retrospective study included one hundred consecutive adult patients undergoing cardiac surgical procedures using tepid modified del Nido cardioplegia. One hundred consecutive adult patients undergoing cardiac surgical procedures with cold blood cardioplegia were the control group. Propensity score matching yielded 89 modified del Nido and 89 cold blood cardioplegia patients. Results: There were no significant differences when comparing the two matched groups regarding the requirement for intraoperative defibrillation (P=0.36), postoperative peak troponin T levels (0.18), perioperative inotropic support (P=0.26), intra-aortic balloon pump requirement (P=0.62), and postoperative left ventricular ejection fraction at discharge (P=0.4) and on the sixth postoperative month (P=0.37). Mean cross-clamping time (P=0.005), cardiopulmonary bypass time (P=0.03), and total operation time (P=0.03) were significantly shorter in the del Nido group. Conclusion: Tepid modified del Nido cardioplegia may be a safe alternative to cold blood cardioplegia in adult patients undergoing cardiac surgical procedures.